SALE AND PURCHASE OF HERITAGE LAND AND BUILDINGS CARRIED OUT WITHOUT THE CONSENT OF THE HEIRS - Agus Armaini Ry (Jurnal Ilmiah METADATA, 2026)
The sale and purchase of inherited land and buildings must be carried out before an authorized public official, namely the Land Deed Drafting Officer, however, problems occurred in making the sale and purchase deed due to objections from the heirs. The procedure for buying and selling land and heritage buildings carried out before the PPAT is that the seller brings the original certificate of title to the land to be sold, KTP (Resident Identification Card), proof of payment of PBB (Building Land Tax), husband/wife's consent letter, for those who are married , KK (Family Card) while the buyer brings their KTP (Resident Identification Card), KK (Family Card), payment money or an order to issue money to the bank as agreed between the seller and the buyer. The legal consequences of the deed of sale and purchase of land and heritage buildings made by PPAT become an authentic deed. The legal force of the deed of agreement is very strong, because the deed of sale and purchase agreement has become a notarial deed so that it is an authentic deed.